One-year evaluation of automated insulin delivery systems in adults with type 1 diabetes - Pujante, Pedro; García, Ana Victoria; Villa-Fernández, Elsa; García-Villarino, Miguel; González-Vidal, Tomás; Díaz-Naya, Lucía; Gutiérrez Buey, Gala; Veiguela, Brenda; Rivas-Otero, Diego; Menéndez-Torre, Edelmiro; Delgado, Elías; Ares, Jessica; et al. (Frontiers in Digital Health, 2025)
IntroductionThis study evaluates the effectiveness of four commercially available automated insulin delivery (AID) systems in routine clinical practice for type 1 diabetes management and compares their first-year outcomes.MaterialsThis retrospective study (October 2020–October 2023) included glucometric data from type 1 diabetes patients collected from the Asturias Automatic Insulin Devices Registry. People with type 1 diabetes using four different AID systems [Minimed™780G (MM780G), Accu-Chek® Insight-Diabeloop (DBLG), Tandem-Control-IQ, and Ypsopump Cambridge HCL-app (Cam-APS)] were included in the study. Primary outcomes were glycaemic control after one year. Secondary outcomes compared the results between the four systems.Results174 patients (60: MM780G, 45: DBLG, 30: Control-IQ, 39: Cam-APS), aged 18–73, predominantly women, were enrolled. At baseline, glycemic control, measured by the achievement of the international consensus targets [TBR (Time Below Range) <4%; TIR(Time in Range) >70% and TAR (Time Above Range) <25%] was only met by 9.72% of participants, while after 1 year of an AID system use, it improved to more than 52%. When comparing between systems, TIR improved significantly after 1 year in all systems. However, Control-IQ did not show improvement in mean glucose and Glucose management index (GMI) and only users of DBLG showed improvement in coefficient of variation (CV). MM780G users achieved the best results after 12 months in mean glucose, TIR and GMI. However, their baseline situation was also better than that of the other groups.DiscussionThis study confirms that, after 12 months of routine clinical use, the use of commercially available automated insulin delivery (AID) systems significantly improves glycemic control in individuals with type 1 diabetes. However, the degree of improvement varies depending on the specific system used.These findings underscore the importance of selecting and optimizing AID systems individually to maximize clinical benefits in type 1 diabetes management.